Video lectures in e-learning: Effects of viewership and media diversity on learning, satisfaction, engagement, interest, and future behavioral intention. Issue 1 (18th April 2017) - Costley, Jamie; Lange, Christopher Henry
Abstract : Purpose: Because student viewership of video lectures serves as an important aspect of e-learning environments, video lectures should be delivered in a way that enhances the learning experience. The delivery of video lectures through diverse forms of media is a useful approach, which may have an effect on student learning, satisfaction, engagement and interest (LSEI), as well as future behavioral intentions (FBI). Furthermore, research has shown the value that LSEI has on learner achievement within online courses, as well as its value in regards to student intention to continue learning in such courses. The purpose of this study is to investigate the relationships between media diversity, LSEI and FBI in hopes of enhancing the e-learning experience. Design/methodology/approach: This study surveyed a group of students ( n = 88) who participated in cyber university classes in South Korea to investigate the correlations between media diversity and lecture viewership, effects of lecture viewership on LSEI and FBI, effects of media diversity on LSEI and FBI as well as the correlation between LSEI and FBI. Findings: Results show no relationship between media diversity and viewership. Both lecture viewership and media diversity were positively correlated with LSEI. However, neither media diversity nor viewership was positively correlated with FBI. Finally, LSEI was positively correlated with FBI. Originality/value: This paper looks at how video lectures affect LSEI. Past research has generally looked at learning, satisfaction, engagement and interest as separate entities that are affected by instructional aspects of online learning. Because of their interrelationships with each other, this study combines them as one construct, making a stronger case for their combined association.